Learned Hand : the man and the judge - Gunther, Gerald, 1927-2002. (New York ; Oxford : Oxford University Press, 2010)
Billings Learned Hand was one of the most influential judges in America. The author procides a complete account of the professional and personal life of leanred hand, conveying the substance and range of his judicial and intellectual contributions.
Includes index.
Description based on online resource; title from home page (viewed Jan. 10, 2011).
Keywords: Hand, Learned, -- 1872-1961.; United States. -- Circuit Court (2nd Circuit) -- Biography; Judges -- United States -- Biography